Residual Income versus Earnings: Which Measure is more Associated with Shareholder Wealth Creation? - Lim, Agnes Geok-Ching (2004)
This study aims to test on an empirical basis which measure, a value-based measure such as residual income (“RI”) or the traditional measure such as earnings, is more closely associated with shareholder wealth creation. Motivation for the study emanates from the increasing emphasis on shareholder wealth creation in Malaysia and interest in the value-based measures for it. It has also been encouraged by Stern Stewart’s recent claim through the Malaysian press that Economic Value Added (“EVA”), an RI concept, is the measure most directly linked to shareholder wealth creation over time. A good performance measure is seen as one which is a good barometer of shareholder wealth creation. A measure which highly correlates with changes in shareholder wealth would appeal to shareholders as it fits into their objective of maximising the value of their investment. Hence, it would be useful to know which of the two performance measures has higher correlation with shareholder wealth creation.The study involves relative and incremental information content tests, carried out by performing annual regression analysis on data covering a 5-year period from year 1999 to 2003. Sample firms comprise listed Malaysian companies which form the Kuala Lumpur Composite Index. Two forms of measures are used for shareholder wealth creation, namely,actual and abnormal share returns. Actual share return takes into account changes in the equity market value and dividends of firms. Abnormal share return refers to actual share return that is in excess of expected return, given the risk of the investment.Our results reveal earnings to be the measure more closely associated with shareholder wealth creation. Supplemental tests indicate that cost of equity has incremental information content in explaining actual share return, but generally not with regards to abnormal return. Further extensions of the incremental tests reveal that past RIs and earnings generally do not add significantly to the information content of current RIs and earnings in explaining shareholder wealth creation. If RI is viewed as a proxy for EVA, our results contradict Stern Stewart & Co.’s claim that EVA is the performance measure most directly linked to shareholder wealth creation, both from the empirical sense and in the Malaysian context. Several implications arise from the study. Firstly, adopters of RI concepts as measures of performance should not expect immediate direct improvements in share returns upon recording high levels of RI. They should also consider using RI as a complementary measure to earnings and not as a single all encompassing measure of the firm, as earnings is seen as the better predictor of shareholder wealth creation. Second, consistent with prior research,our results show generally low R2s and that approximately 70% of shareholder wealth creation is explained by factors other than the performance measures. This suggests that shareholders might have to search for a different measurement paradigm altogether if they require a performance measure that is more highly correlated with shareholder wealth creation